Virtual Reality: An Exploration of Student and Teacher Perceptions of a Virtually Delivered Mindfulness Curriculum in Undergraduate Medical Education - Bailey, Karen; Patel, Kush; Sanchez-Campos, Millaray; Gonsalves, Carol; MacLean, Heather (The International Journal of Whole Person Care, 2025)
Background: The COVID-19 pandemic caused a mandatory shift to virtual delivery of content in medical education. This study explored the benefits and limitations of a virtually delivered mindfulness curriculum as perceived by students and teachers. Our goal was to identify key concepts to consider for improving or implementing such a curriculum at the undergraduate medical education level.Methods: This was a mixed methods research study. An online questionnaire was administered and focus group interviews were conducted. Conventional content analysis was used to code and derive themes from interview transcripts.Results: The perceptions of 35 first- and second-year medical students and five mindfulness teachers were collected. A qualitative thematic analysis of interview transcripts identified positive features of virtual delivery which included ‘convenience’, ‘accessibility’, and ‘a less intimidating environment’. Negative features included ‘decreased connection and sense of community’, ‘less accountability’, ‘susceptibility to distractions’, and ‘screen fatigue’. Many students proposed a hybrid of in-person and virtual teaching as an ideal curriculum.Conclusion: Future efforts for developing or refining mindfulness curricula for medical trainees may benefit from further investigating the unique advantages of both virtual and in-person delivery methods and how they may uniquely support wellbeing and professional satisfaction.